2016
DOI: 10.1161/circulationaha.115.018926
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cardiac Rehabilitation With Stress Management Training

Abstract: Background Cardiac rehabilitation (CR) is the standard of care for patients with coronary heart disease (CHD). Despite considerable epidemiologic evidence that high stress is associated with worse health outcomes, stress management training (SMT) is not included routinely as a component of CR. Methods and Results 151 outpatients with CHD aged 36 to 84 years were randomized to 12-weeks of comprehensive CR or comprehensive CR combined with SMT (CR+SMT), with assessments of stress and CHD biomarkers obtained be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(200 citation statements)
references
References 55 publications
7
170
1
13
Order By: Relevance
“…However, as previously reported, self-reported activity was significantly associated with objectively measured physical activity using actigraphy-assessed physical activity, collected both at baseline and again following 3-months of CR after controlling for demographic characteristics and medical comorbidities. [10] Second, only 80% of participants were available at follow-up, although our findings were not altered when missing data were accounted for statistically using multiple imputation. Third, we were unable to obtain data on other possible psychological treatments during the 1-year follow up period (e.g., psychotherapy, psychotropic medication, etc.)…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, as previously reported, self-reported activity was significantly associated with objectively measured physical activity using actigraphy-assessed physical activity, collected both at baseline and again following 3-months of CR after controlling for demographic characteristics and medical comorbidities. [10] Second, only 80% of participants were available at follow-up, although our findings were not altered when missing data were accounted for statistically using multiple imputation. Third, we were unable to obtain data on other possible psychological treatments during the 1-year follow up period (e.g., psychotherapy, psychotropic medication, etc.)…”
Section: Discussionmentioning
confidence: 69%
“…The CR+SMT condition was comprised of standard CR plus weekly, group-based SMT sessions t. [15] The methods and primary results of the trial have been reported previously. [10] The present report describes results for data collected nine months after completing CR (i.e., 12-months following randomization).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, only a handful of studies have examined the impact of CR on patients’ physical and emotional recovery from SCAD. 1719 More information regarding SCAD patients’ experience with CR is needed to better meet the needs of this population subset.…”
mentioning
confidence: 99%
“…Thus, novel approaches for improving psychological functioning should be considered. For example, programs focusing on exercise and comprehensive lifestyle changes (e.g., stress management training combined with cardiac rehabilitation) have been shown to improve mental and physical health [119121]. Given the evidence linking positive well-being to better health outcomes, efforts to target positive well-being may serve as important components of broader CVD management programs.…”
Section: Discussionmentioning
confidence: 99%